Reading the Meaning of the Realization of a Residential House in Tenganan Pegringsingan Village, Bali using the Hermeneutic Method - Agustin, Selvia Noer; Saraswati, A.A. Ayu Oka (ASTONJADRO, 2024)
Discussion of traditional architecture is still interesting to do because of the high meaning in it. Including traditional Balinese architecture, more precisely the house in Tenganan Pegringsingan Village. The house for the indigenous people of Tenganan Pegingsringan Village consists of several building periods, including Bale Buga, Sanggah, Bale Meten, Bale Tengah and Paon. The aim of the study was to analyze the meaning of the embodiment of a residential house in Tenganan Pegringsingan Village, Bali using the hermeneutic method. The research method used is a qualitative method with primary data from direct observation in the form of photographs, interviews and secondary data from literacy which is then compiled, the two data can be analyzed using a hermeneutic approach to obtain results and conclusions. The meaning of the house in the village of Tenganan Pegingsringan was born from the activities of its users who have the same values and expressions. Different users from community groups based on village manners have the same residential meaning. The meaning of the house form in Tenganan Pegingsringan Village has ritual, symbolic, ethical, religious and sustainable meanings.